Regulation of CHK1 inhibitor resistance by a c-Rel and USP1 dependent pathway. Issue 19 (14th October 2022) - Hunter, Jill E.; Campbell, Amy E.; Hannaway, Nicola L.; Kerridge, Scott; Luli, Saimir; Butterworth, Jacqueline A.; Sellier, Helene; Mukherjee, Reshmi; Dhillon, Nikita; Sudhindar, Praveen D.; Shukla, Ruchi; Brownridge, Philip J.; et al.
Abstract : Previously, we discovered that deletion of c-Rel in the Eµ-Myc mouse model of lymphoma results in earlier onset of disease, a finding that contrasted with the expected function of this NF-κB subunit in B-cell malignancies. Here we report that Eµ-Myc/ cRel −/− cells have an unexpected and major defect in the CHK1 pathway. Total and phospho proteomic analysis revealed that Eµ-Myc/ cRel −/− lymphomas highly resemble wild-type (WT) Eµ-Myc lymphomas treated with an acute dose of the CHK1 inhibitor (CHK1i) CCT244747. Further analysis demonstrated that this is a consequence of Eµ-Myc/ cRel −/− lymphomas having lost expression of CHK1 protein itself, an effect that also results in resistance to CCT244747 treatment in vivo . Similar down-regulation of CHK1 protein levels was also seen in CHK1i resistant U2OS osteosarcoma and Huh7 hepatocellular carcinoma cells. Further investigation revealed that the deubiquitinase USP1 regulates CHK1 proteolytic degradation and that its down-regulation in our model systems is responsible, at least in part, for these effects. We demonstrate that treating WT Eµ-Myc lymphoma cells with the USP1 inhibitor ML323 was highly effective at reducing tumour burden in vivo . Targeting USP1 activity may thus be an alternative therapeutic strategy in MYC-driven tumours.